2022
DOI: 10.1021/acs.jpcc.2c00578
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupolar Isotope-Correlation Spectroscopy in Solid-State NMR

Abstract: Quadrupolar solid-state NMR carries a wealth of structural information, including insights about chemical environments arising through the determination of local coupling parameters. Current methods can successfully resolve these parameters for individual sites using sample-spinning methods techniques applicable to quadrupolar I ≥ 1 nuclei, provided second-order central transition broadenings do not exceed by much the spinning rate. For large quadrupolar coupling ( C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…For L-histidine.HCl.H2O deuterated from water-d at room temperature (295 ±3 K), the H/D exchange yields are in the range of 20-36% for different labile sites such as -NH in the heterocycle, NH3 and water protons, however, a high degree of H/D exchange of up to 90% can be obtained by recrystallizing the same compound at elevated temperatures. [19] Relatively high yields of deuteration and shorter relaxation delays associated 2 H sites allow us to rapidly detect a 2 H MAS spectrum (Figure 1b), in which the water-D, ND3 and the D7/D5 peaks (10)(11)(12)(13)(14)(15)(16)(17)(18) ppm are observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For L-histidine.HCl.H2O deuterated from water-d at room temperature (295 ±3 K), the H/D exchange yields are in the range of 20-36% for different labile sites such as -NH in the heterocycle, NH3 and water protons, however, a high degree of H/D exchange of up to 90% can be obtained by recrystallizing the same compound at elevated temperatures. [19] Relatively high yields of deuteration and shorter relaxation delays associated 2 H sites allow us to rapidly detect a 2 H MAS spectrum (Figure 1b), in which the water-D, ND3 and the D7/D5 peaks (10)(11)(12)(13)(14)(15)(16)(17)(18) ppm are observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a handful of studies have reported the solid-state 2D correlation NMR spectra of isotopes of the same nuclei. [18,19] The limitations arise from the Larmor frequencies of many of these isotopes being too close together to be separated and simultaneously tuned in NMR probes, or due to the large differences in their natural abundance or nuclear spin properties (I = ½ and I >½ ) or a combination of these. For example, spins with large quadrupolar interactions require specific pulse sequences to excite and correlate them in a 2D NMR experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDI is already in use by several groups and underlies the processing of data in multiple publications over the past several years [14][15][16][17][18][19][20] . To facilitate its widespread dissemination, the current manuscript describes the general philosophy behind the framework, and its main classes and the way they interact among themselves.…”
Section: Introductionmentioning
confidence: 99%